CONSUMER STATISACTION AND THE PRINCIPLES OF ITS FORMATION INTHE LATVIA HEALTH CARE MARKET (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Consumer satisfaction is a key aspect of business success, as it directly affects consumer loyalty, promotion of cooperation, as well as company recommendations and positive feedback. It refers to the extent to which the products, services and experiences offered by a company meet or exceed consumer expectations and needs. Consumer satisfaction is influenced by various factors, which can mostly be considered subjective. Researchers have developed several customer satisfaction metrics that can help companies improve and promote successful business. The aim of the study is to assess consumer satisfaction with the Latvian healthcare system. To achieve the set research objective, the theoretical part was analysed using the monographic or descriptive method, while the primary data was obtained through a survey. The study provides an understanding of the feasibility of medical tourism in the Latvian economy. The results of the study will provide an opportunity to understand the feasibility of medical tourism in Latvia.